Paroxysmal Sympathetic Hyperactivity - Scott, Rachael A.; Rabinstein, Alejandro A. (Seminars in Neurology, 2020)
Paroxysmal sympathetic hyperactivity (PSH) is a relatively common, but often unrecognized, complication of acute diffuse or multifocal brain diseases, most frequently encountered in young comatose patients with severe traumatic brain injury. It is presumed to be caused by loss of cortical inhibitory modulation of diencephalic and brain stem centers and possible additional maladaptive changes in the spinal cord that combine to produce exaggerated sympathetic responses to stimulation. The syndrome consists of repeated sudden episodes of tachycardia, tachypnea, hypertension, sweating, and sometimes fever and dystonic posturing. The diagnosis is clinical. Treatment includes reducing any external stimulation that can trigger the episodes, and starting abortive (e.g., intravenous morphine) and preventive medications (e.g., gabapentin, propranolol, clonidine). Prompt and adequate treatment of PSH may reduce the likelihood of secondary complications, such as dehydration, weight loss and malnutrition, and muscle contractures.
Keywords: paroxysmal sympathetic hyperactivity; dysautonomia; autonomic storms; hypertension; tachycardia